Discreet 3ds Max 7 - Hurwicz, Michael; Virtual Training Company ([Australia] : Virtual Training Company, 2008)
This video guide users through visualization, construction and animation of our own 3D projects and characters, utilizing 3ds max 7's improved character creation and animation features
Title from container
Training CD
Contains 227 movies with total time 12 hours
System requirements: Mac: System 9 or higher ; PC: Windows 98 or higher, 32MB System RAM, 6MB Video RAM, 16x CD-ROM ; QuickTime 6
Keywords: MAX 3ds 7.0; Computer graphics; Computer animation